Comparison of Histology Practicum Exam Results Based on the Learning Style of Medical Students - Sumargo, Kuni Zakiyyah; Hasanuddin, Abdi Dzul Ikram; Yusuf, Muhamad Nur Syukriani; Pateda, Andin Zahrani; Lestari, Putri Ayu Eka (Universitas Gadjah Mada, 2024)
Background: Histology is one of the essential subjects to be understood in medicine. Identifying the appropriate learning styles can be a solution to improve learning performance and achieve maximum learning outcomes.Aims: This study aims to determine the effectiveness of learning styles on histology practical exam results in medical students.Methods: This study used a cross-sectional design by involving students at the medical faculty of Universitas Negeri Gorontalo who contracted the biomedical course I in the 2022/2023 academic year. Learning styles are assessed using a visual-auditory-kinesthetic (VAK) questionnaire to categorize student learning styles. The results of the practicum exam in the form of numbers are obtained from the accumulated scores of the first practicum exam in histology with the topics of cytology, epithelium, and connective tissue. The one-way ANOVA test was conducted to analyze the data.Results: Out of 42 participants involved, visual, auditory, and kinesthetic learning styles were 18 people (42.9%), 23 people (54.8%), and 1 people (2.4%), respectively. Generally, the student practicum exam results were 63.62 ± 17.24. Based on the learning styles group of visual, auditory, and kinesthetic, the mean (SD) practicum exam results were 66.00 (14.60), 62.43 (19.29), and 48.00 (0.00), respectively (p-value = 0.541).Conclusion: Visual learning style shows marginally better practicum exam results than other learning styles. This result can be considered a learning strategy to improve the results of practicum exams, particularly in the subject of histology practicum courses.